2020
DOI: 10.17352/ijsrhc.000011
|View full text |Cite
|
Sign up to set email alerts
|

Young people’s experiences in accessing sexual and reproductive health services in sub-Saharan Africa from 1994 to 2019 - A content analysis

Abstract: Two and a half decades after the International Conference on Population and Development in 1994, access to Sexual and Reproductive Health (SRH) services by young people is very low, particularly in sub-Saharan Africa (SSA) despite the increasing resources being targeted at addressing the SRH needs of young people. This paper focuses on the needs and experiences of young people in accessing SRH services in SSA. Using a content analysis tool, this paper focused on review of published articles on barriers to SRH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
3
10
0
Order By: Relevance
“…The cost factor led to the reliance on borrowed or shared phones by people who could not afford to be able to access SRH services. The use of borrowed and shared phones resulting in privacy and confidentiality challenges was also reported in this study [72,105,119,120,157,162,163,168,173] with high confidence in the study findings noted. Mobile phone sharing is a common phenomenon across rural settings in LMICs among poor young people and creates potential source of privacy and confidentiality breaches (60)(61)(62)(63).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The cost factor led to the reliance on borrowed or shared phones by people who could not afford to be able to access SRH services. The use of borrowed and shared phones resulting in privacy and confidentiality challenges was also reported in this study [72,105,119,120,157,162,163,168,173] with high confidence in the study findings noted. Mobile phone sharing is a common phenomenon across rural settings in LMICs among poor young people and creates potential source of privacy and confidentiality breaches (60)(61)(62)(63).…”
Section: Discussionsupporting
confidence: 74%
“…These social beliefs need to be addressed to avoid misinforming young people for using the mobile phone technology for SRH information and services in rural context of LMICs. Public education is critical to educate rural populations about mHealth SRH initiatives to address knowledge gaps in relation to myths and perceptions that affect use of mobile phone platforms for SRH information and services among young people in rural contexts in LMICs (72, 73).…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has demonstrated that high rates of HIV and SRH service utilization among adolescents could be achieved by providing these HIV and SRH services within schools (11,32–34). In light of this evidence, the South African government has taken steps towards providing HIV and contraceptive services in schools under the Integrated School Health Programme (12). Not only is there resistance to this from some parents, it is difficult to implement and resource intensive.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Negative attitudes of health workers have been reported to constitute significant barriers to the utilization of SRH services by adolescents when available. [9][10][11][12][13][14][15] As a result of these difficulties in access to SRH services, many adolescents lack adequate knowledge and skills to enjoy optimal SRH leading to health problems such as unwanted pregnancy, unsafe abortion and sexually transmitted infections including HIV/AIDS which are associated with a higher maternal mortality and morbidity in adolescents. [8,16] The assessment of tertiary-level health workers' perception and attitude towards the provision of SRH services to unmarried adolescents in Plateau State, Northcentral Nigeria has not been adequately investigated.…”
Section: Introductionmentioning
confidence: 99%